Sustainability Analysis At KnK Koffee Resources - Wahyudin, Agus; Pramono Sari, Maylia; Maftukhah, Ida (Indonesian Journal of Devotion and Empowerment, 2024)
MSMEs become one of the backbones of the national economy have enormous economic potential. Semarang City has 17,564 MSMEs (95%) and in the last five years, the turnover of MSMEs assisted by the Central Java Provincial Government has increased by Rp. 30.45 trillion. However, that does not mean that MSMEs do not encounter obstacles. This obstacle is exacerbated by the conditions of the Corona Virus Disease 2019 (Covid-19) Pandemic, the majority of business people experiencing a decline in turnover. The MSMEs affected by the pandemic are approximately 1,538 MSMEs, as many as 50% of MSMEs are food processing, and the remaining 50% are mixed MSMEs. It is necessary to assist the Community Service Team of the State University of Semarang (PPM Unnes) with the target audience of MSMEs in the City of Semarang, namely Strengthening Knk Koffee Resources Partners. This home-based coffee processing industry is a café stockist from 60 coffee shops (75% supplier) in Semarang, with an average turnover of 100 million per month. This activity is in line with the Regional Medium-Term Development Plan (RPJMD) of Semarang City for 2016-2021. The community/locality development (CD/LD) model used includes community services, empowering, and relations, with the stages of collecting facts, problem formulation, program planning, action and communication, and evaluation. This activity is expected to improve the quality of partners/MSMEs by increasing the competitiveness, production, turnover and welfare of partners. Government support, research institutions and banks with motivating forces, credit, upkeep gear, and quality standard help will increment efficiency and quality whereas expanding smallholder coffee costs.